Memórias da escola rural : representações da cultura escolar da Escola Rural Mista de Bom Sucesso na memória de ex-alunos e uma ex-professora (1937 – 1952) - Silva, Silvana Maria da (2018)
The research is an investigation in the Education History field that focus in the rural education. It aims to analyze the rural educational scene in Mato Grosso and to understand the representations about the school culture of the Mixed-sex Rural School of Bom Sucesso in the memories of former students and a former teacher, between the years 1937 – 1952. The research tried to answer the following question: Which are the representations of the school culture that are reside in the memories of former students and a former teacher in the Mixedsex Rural School of Bom Sucesso during 1937 – 1952? To answer the problematizated question and achieve the objectives of the research, it used a theoretical approach based in Cultural History. It used the Oral History as the methodological option because it provides the memory record that can help in interpretation of the past. Therefore, the testimony of three former students and of a former teacher of the Mix-sexed Rural School of Bom Sucesso were used joined by the following documents: laws, decrees, regulations, messages of the governors, trades, certificates, books of the school audit, maps of the school audits. All the documentary sources were localized in the Publich Archive of Mato Grosso (APMT), and in the History Education and Memory Group GEM/IE/UFMT, and in a few private archives. The former students and the former teacher narrated the memories showing that they miss those times even tough they have experienced a lot of difficulties in the narrated period. It was testified by this research that the representations of the school culture in the memories of the former students and the former teacher were marked by the rigidity of the teaching process. It was demanded from them a rigorous routine in which it was necessary a lot of effort to achieve the knowledge and the memorization process was the main learning strategy. By this sense, the responsibility for the school advancement was assigned almost exclusively to the student.